A low-noise readout circuit design for multi-bit quanta image sensor. (July 2022) - Wang, Xiuyu; Li, Changchun; Zha, Wanbin; Nie, Kaiming; Xu, Jiangtao
Abstract: This paper presents a novel readout circuit based on low-noise charge transfer amplifier (LCTA) to suppress the readout noise in multi-bit quanta image sensor. A switched capacitor circuit is used in LCTA to reduce the kT/C noise introduced by its load capacitor, and make the noise from ADC further suppressed due to the increase of its output swing. The digital correlated double sampling of single-slope ADC is used to eliminate the fixed noise in LCTA. The low noise readout circuit is implemented by a 110 nm CMOS process. The simulation results show that the random noise of LCTA is reduced by 19% at a gain of 2 V/V compared to the conventional differential charge transfer amplifier. The increased output swing reduces the random noise power of ADC by 61%. In addition, the LCTA equivalent input fixed noise with 29.8 μVrms is eliminated. The proposed low-noise readout circuit improves the signal-to-noise ratio by 4.37 dB at small-signal conditions.